USE OF ALLELE-SPECIFIC MARKERS OF THE PPD AND VRN GENES FOR PREDICTING GROWING SEASON DURATION IN BARLEY CULTIVARS - M. M. Zlotina; O. N. Kovaleva; I. G. Loskutov; E. K. Potokina (Вавиловский журнал генетики и селекции)
Allelic combinations of the Vrn-H1, Vrn-H2, Vrn-H3, Ppd-H1, and Ppd-H2 genes have been investigated with allele-specific molecular markers in 91 spring barley cultivars recommended for use in Russia and Belarus. In a field experiment under conditions of North-West Russia, heading date evaluation has been performed in these cultivars.Barley varieties having the dominant Ppd-H1 allele were shown to overrun other genotypes in the developmental rate (heading date) and to mature earlier under long-day conditions. Among studied cultivars, grown in Russia, only 9 % possessed the dominant Ppd-H1 allele. A significant association was also found between the allele combination of Vrn genes and heading date of barley cultivars. Among cultivars with identical genotypes for Ppd-H1 and Ppd-H2, those having the allelic combination Vrn-H1vrn-H2Vrn-H3 flower significantly earlier than with other haplotypes. The use of allele-specific markers of Ppd and Vrn genes makes breeding for early ripeness easier and faster.